DISTRIBUTION PATTERN OF MANGROVE Shells (POLYMESODA) IN MANGROVE ECOSYSTEM AREA SETIA BAKTI DISTRICY ACEH JAYA - Indah Lestari; M. Ali S; Ismul Huda; Abdullah Abdullah; Safrida Safrida (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
ABSTRACTPolymesoda one of the groups of shells that live in mangrove ecosystems, Polymesoda has a role for the environment in recycling organic matter, the mineralization process, maintaining the balance of the food chain and as a detritus eater. This study aims to analyze the distribution patterns of Polymesoda in the Mangrove Ecosystem in the Setia Bakti District Aceh Jaya District. The study was conducted in January 2020 and retrieved data using a survey method with a purposive sampling technique. The study was conducted in two areas with three locations, with each station made of three stations and five sampling plots for each station. Distribution patterns were analyzed using the Morisita Index formula. The results obtained are the distribution patterns ranging from 1.0 -1, 76. The conclusion was obtained that the distribution pattern in the Mangrove Ecosystem of the Setia Bakti District of Aceh Jaya Regency is at location I and location III namely Clustering and at location II that is random.Keywords: Morisita, Polymesoda, Setia BaktiABSTRAKPolymesoda salah satu kelompok kerang yang berhabitat di kawasan ekosistem  mangrove,  Polymesoda ini memiliki  peranan bagi lingkungan sebagai  pendaur ulang bahan organik, dalam proses mineralisasi dan menjaga keseimbangan rantai makanan dan sebagai pemakan detritus. Penelitian ini bertujuan Untuk menganalisis  pola distribusi Polymesoda di Kawasan Ekosistem Mangrove Kecamatan Setia Bakti Kabupaten Aceh Jaya. Penelitian dilakukan pada bulan Januari 2020, dan mengambil data menggunakan metode surve dengan teknik purposive sampling. Penelitian dilakukan pada dua kawasan dengan tiga lokasi yang masing-masing lokasi dibuat tiga stasiun dan pada setiap stasiun ditetapkan lima plot sampling. Pola  distribusi dianalisis dengan rumus Indeks Morisita,. Hasil yang didapatkan yaitu pola distribusi berkisar dari 1,0 -1, 76. Kesimpulan diperoleh bahwa Pola distribusi di Kawasan Ekosistem Mangrove Kecamatan Setia Bakti Kabupaten Aceh Jaya adalah pada lokasi I dan lokasi III yaitu Mengelompok dan Pada lokasi II yaitu acak .Kata Kunci : Morisita, Polymesoda, Setia Bakti